Зольники белогрудовского типа – сложные монументальные структуры эпохи поздней бронзы - Гершкович, Я.П. (Археологический альманах, 2009)
It is necessary to consider the mode of their forming and archaeologization when some unaccountable monumental archaeological sites are being discussed. Such approach allows to explain an essence of so-called ash-heaps (zolniks) of the Beloogrudovka type which were spread in the Late Bronze Age on southwest of Eastern Europe in the Noya, Sabatinovka, Belogrudovka cultures, etc. The problem is: they have features of both productive-domestic sites, and sacral places. Ash-heaps of the Belogrudovka type are complex monumental structures, but on the initial stage they were productive-domestic ones. In spite of the fact that there are separate traces of ritual actions in them, it is impossible to consider their as sanctuaries or constantly existing altars, because such features are secondary here and connected with disposable short-term actions.